Organochlorine Levels in Plasma and Risk of Multiple Myeloma - Weber, L.; Song, K.; Boyle, Terry; Gaudreau, .; Lai, A.; Sutherland, H.; LeBlanc, A.; Spinelli, J. (2018)
CONCLUSION: Our study provides evidence that organochlorines contribute to the risk of MM.RESULTS: Most organochlorine analytes showed a significant association with MM. The strongest association (highest vs lowest quartile) was oxychlordane (odds ratio?=?7.44; 95% confidence interval?=?4.19 to 13.21). No heterogeneity was detected between organochlorines levels and MM subtypes. Only oxychlordane and ß-hexachlorocyclohexane (ß-HCCH) were identified as significant independent predictors of MM.OBJECTIVE: The aim of this study was to estimate the association between organochlorine pesticides and polychlorinated biphenyls (PCBs) and multiple myeloma (MM).METHODS: The risk of MM from organochlorine compounds was examined in a population-based case-control study in British Columbia, Canada. Congeners of PCBs and pesticides or pesticide metabolites were measured in plasma of 325 cases and 327 controls.